Application of Storytelling in political public relations - Tesanovic, Natasa (Sociološki godišnjak, 2023)
Storytelling is one of the techniques in public relations. Its application is based on man’s need to transpone life into stories and psychological mechanisms that make people think through metaphors and share a common experience through mythical and archetypal motifs deeply embedded in their collective unconscious. Sociological observations of narratives emphasize the important role of stories in the construction of the self and collectivity, in the establishing and maintenance of social authorities, while treating the story as a critical and even liberating discursive form. Global insecurity and modern technologies have increased the use of webcasting in various media, which, in the era of information blizzard, identity hyperproduction and the tribal character of the Internet, turns out to be an effective tool for the promotion of political candidates, for which this research offers a number of illustrative examples from different political and cultural milieus